PENGALAMAN PSIKOLOGIS KE PANTAI SEBAGAI MEDIA COPING STRESS PADA REMAJA DI KOTA KUPANG - Regina Wahyu Seravia (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The high rate of psychological stress and emotional distress due to academic burdens and social relationship crises underlie this research. These operational issues trigger mental burnout, sleep disturbances, and the inability of adolescents to independently manage daily emotional turmoil in Kupang. The main focus of this scientific study is to examine the psychological experience of coastal recreation as a draft stress coping strategy for adolescents. This exploratory qualitative research process utilized structured in-depth interviews with 4 adolescent sample respondents legally domiciled in Kupang City, aged 15 to 24, selected using purposive sampling techniques. The qualitative data processing procedure was executed in a structured manner using a six-stage thematic analysis, starting with descriptive coding and member check verification. The qualitative research findings revealed that coastal recreation occurs once or twice a week, combining emotion-focused coping strategies through sharing stories with peers and problem-focused coping through completing academic assignments in stages. The coastline has proven to be a means of healing, a source of inner calm, a provider of relaxation, and a support for local spiritual resilience prior to ordination. The main conclusion confirms that utilizing public open spaces is highly reliable as a sustainable media strategy for mental health recovery for the younger generation. ABSTRAK Laju tekanan psikologis dan tingginya ketertekanan emosional akibat beban akademik serta krisis relasi sosial melatarbelakangi kegiatan penelitian ini. Masalah operasional tersebut memicu timbulnya kejenuhan mental, gangguan tidur, serta ketidakmampuan remaja dalam mengelola gejolak emosi secara mandiri harian di Kupang. Fokus utama kajian ilmiah ini adalah membedah pengalaman psikologis rekreasi ke kawasan pesisir sebagai draf strategi coping stress pada remaja. Langkah-langkah penelitian kualitatif eksploratif ini dioperasikan menggunakan interaksi wawancara mendalam terstruktur pada 4 orang sampel remaja berusia 15 hingga 24 tahun di Kota Kupang yang dipilih menggunakan teknik purposive sampling. Prosedur pengolahan data kualitatif dieksekusi secara terstruktur memakai analisis tematik enam tahapan yang diawali dari pembuatan kode deskriptif hingga verifikasi member check. Temuan riset secara kualitatif menyingkap bahwa rekreasi ke pantai dilakukan dengan frekuensi 1 hingga 2 kali sepekan, mengombinasikan strategi emotion-focused coping via aktivitas berbagi cerita bersama rekan serta problem-focused coping dengan menyelesaikan tugas akademik secara bertahap. Pesisir laut terbukti menjadi sarana healing, penenang batin, penyedia efek relaksasi, serta penopang ketahanan spiritual lokal sebelum pentahbisan sidi. Simpulan utama menegaskan bahwa pemanfaatan area terbuka publik sangat andal sebagai draf media pemulihan kesehatan mental generasi muda secara berkelanjutan.